Estudo de caso de um programa de aceleração de empresas do segmento de saúde no contexto brasileiro - Paulo Adriano Freitas Borges (2020)
Prior research have pointed out accelerators as a prominent actor in the development of startups, since, they provide mentoring, connections and access to investments in a structured way. Healthcare sector startups, however, have a very peculiar development path, as this sector requires high investment values, a longer development period and is still heavily regulated. Few studies address a specific acceleration model for healthcare companies. The challenge, therefore, is try to understand which aspects should be included in an acceleration program for companies in the healthcare sector. To this end, this exploratory research prepared as a case study on an acceleration program and, observed for sixteen months, the development of nine accelerated startups in view of the activities proposed in the program. It was possible to verify the importance of having a specialized and qualified acceleration team, a vast network of mentors, training programs that adapt to the needs of the startup, national and international network aligned with the thematic areas of the sector, laboratory infrastructure and production facilities for shared use and broad access to a global network of specialized investors. Few acceleration programs are currently able to offer the set of characteristics necessary for the development of health startups. This work is expected to contribute to the evolution of acceleration programs for companies in the health sector in Brazil.